Diagnóstico de los factores que impiden el desarrollo turístico del Sector Recreo del Congo, Cantón Buena Fe, año 2019 - Arreaga Mora, Narcisa Elizabeth (2020)
The present work known diagnosis of the factors that prevent the tourist development of the sector "Recreation of Congo", canton Buena Fe, year 2019. is based on the little interest that this sector is placed in the needs of tourism development. Provincial tourism development is considered and a mandatory crossing point to go to the different parts of the Ecuadorian territory, in addition to having limitations that are exploited in a responsible way will contribute positively to its economic growth, this has not been given which we It makes us realize that there is very little interest on the part of the main actors in the tourist environment to help boost tourism in that sector. For the development of the investigation, an explanatory investigation will be required to try to determine the causes and consequences of the current situation of the factors that influence tourism development and quantitative research to make a study of reality through the techniques of Collection of data such as observation, interview and surveys which help us reach the conclusions and final recommendations.